دور وحدات المراجعة الداخلية في تحسين كفاءة عمل لجان التدقيق المنبثقة عن مجالس الإدارة في الشركات المساهمة العامة الأردنية (دراسة ميدانية) - الشواورة, فيصل محمود; الشقاحين, رياض مصلح (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف هذا البحث إلى دراسة وتحليل دور وحدات المراجعة الداخلية في تحسين كفاءة لجان التدقيق المنبثقة عن مجالس الإدارة في الشركات المساهمة العامة الأردنية، لاسيما وأن وجود وحدة مراجعة داخلية فعاله وقوية من شأنه أن يعزز من دور لجان التدقيق ويقي ويحصن أصحاب المصالح المختلفة من تلقي واستخدام قوائم مالية صورية أو وهمية، قد تقودهم بالنتيجة إلى اتخاذ قرارات استثمارية وتمويلية خاطئة وغير محمودة العواقب. وباستخدام أدوات الإحصاء الوصفي (المتوسط الحسابي، والانحراف المعياري واختبار مان ونتي) والحزمة الإحصائية (SPSS) فقد توصلت الدراسة إلى أن معظم العناصر التي يتكون منها الإطار المرجعي لوحدات المراجعة الداخلية إذا ما أحسن إدارتها وتنفيذها بشكل فعال سوف تؤدي بالتبعية إلى رفع وتحسين كفاءة عمل اللجان المنبثقة عن مجالس الإدارة . This research aims to examine and analyze the role of internal audit units in improving the efficiency of the audit committees stemming from the Boards Of Directors (BOD) within the context of the Jordanian public shareholding companies, especially since the existence of an effective and strong internal audit unit will enhance the role of audit committees and protect the different stakeholders from receiving and using fake financial statements that might lead them to take wrong or ineffective investment and finance decisions that lead to undesirable consequences. By using SPSS tools and mainly descriptive statistics (arithmetic mean, standard deviation and test of Man Wenty the study revealed that most of the elements that make up the frame of reference for the internal audit units, if properly managed and implemented effectively will lead consequently to improve the efficiency of the work of the committees stemming from the BOD.